“IT IS HER DECISION, NOT MINE” THE PROBLEM OF CHOICE IN ABORTION CONSULTATION SERVICES IN NORWAY - Anggia, Franceline (Paradigma: Jurnal Kajian Budaya, 2022)
Since 1978, women have been granted legal rights to self-determined abortion, from which the idea of women’s right to choose achieves its victory in the current Norwegian abortion law. Behind this notion of choice lies an assumption that perceives women as subjects of choice who should personally decide whether or not having an abortion would be the proper way to overcome difficult decisions on their pregnancies. Women’s right to choose is celebrated as an ideal concept in consultation services for women who face difficult decisions on whether or not to have an abortion. Counselors and health workers I interviewed used the notion of women’s right to choose to describe the professionalism of their work; that is, to create distance from a woman’s decision-making process. By employing engaged listening to collect ethnographic data, this study explores limitations encountered with the idea of women’s right to choose as applied to care practices for women who are uncertain about their pregnancies. This inquiry examines care relations formed under conditions where the notion of individual choice is not ideal in practice. This study shows how individual choices are socially bound. Women’s status as subject of choice is not predetermined but enacted through emotional labor performed by healthcare professionals, which could affect clients’ openness and self-efficacy to enact a choice. Emotional labor challenges the claim of neutrality which was described as being emotionally detached from clients, as emotion itself is often deemed insignificant for making rational decisions.